2022
DOI: 10.3389/fmicb.2021.782523
|View full text |Cite
|
Sign up to set email alerts
|

An Endophytic Strain of Bacillus amyloliquefaciens Suppresses Fusarium oxysporum Infection of Chinese Wolfberry by Altering Its Rhizosphere Bacterial Community

Abstract: Root rot disease is a serious infection leading to production loss of Chinese wolfberry (Lycium barbarum). This study tested the potential for two bacterial biological control agents, Bacillus amyloliquefaciens HSB1 and FZB42, against five fungal pathogens that frequently cause root rot in Chinese wolfberry. Both HSB1 and FZB42 were found to inhibit fungal mycelial growth, in vitro and in planta, as well as to promote the growth of wolfberry seedlings. In fact, a biocontrol experiment showed efficiency of 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 87 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…Our work proved that F. tricinctum was the pathogen causing bulbs rotting and spalling from the basal disc, as well as progressive yellowing and defoliation of the leaves in lilies and Lanzhou lilies ( Li et al, 2013 ; Shang et al, 2014 ). Interestingly, we also found that F. tricinctum was involved in root rot of Chinese herbal medicine, e.g., Angelica sinensis and wolfberry ( Liu et al, 2021 ; Uwaremwe et al, 2022 ).…”
Section: The Distribution and Ecology Of Fusarium Tricinctummentioning
confidence: 73%
See 1 more Smart Citation
“…Our work proved that F. tricinctum was the pathogen causing bulbs rotting and spalling from the basal disc, as well as progressive yellowing and defoliation of the leaves in lilies and Lanzhou lilies ( Li et al, 2013 ; Shang et al, 2014 ). Interestingly, we also found that F. tricinctum was involved in root rot of Chinese herbal medicine, e.g., Angelica sinensis and wolfberry ( Liu et al, 2021 ; Uwaremwe et al, 2022 ).…”
Section: The Distribution and Ecology Of Fusarium Tricinctummentioning
confidence: 73%
“…The biological activity of these strains is often related to the production of secondary metabolites, such as antimicrobial cyclic lipopeptides ( Dunlap et al, 2011 ). Our research shows that Bacillus amyloliquefaciens has good control effects on root rot infested by F. tricinctum in Chinese herbal medicine of Angelica sinensis , Lanzhou Lilies, and wolfberries ( Shang et al, 2016 ; Liu et al, 2021 ; Uwaremwe et al, 2022 ). B. amyloliquefaciens strains were found to inhibit F. tricinctum fungal mycelial growth, in vitro and in planta , as well as to promote the growth of seedlings ( Liu et al, 2021 ; Uwaremwe et al, 2022 ).…”
Section: Disease Control To Fusarium Tricinctummentioning
confidence: 79%
“…Specifically, integrated Bacillus-derived biofertilizer application after ammonia fumigation was highlighted to be an alternative strategy for reconstructing soil microbiome and suppressing banana Panama disease, which can further deplete pathogen abundance and reduce disease incidence (Shen et al, 2019); in detail, although the abundance of Bacillus (including the inoculated strain) did not significantly increase after biofertilization, putative beneficial taxa, such as Paenibacillus, Virgibacillus, Nitrosomonas, and Nitrobacter, were significantly enriched by fumigation and biofertilizer application and were significantly correlated with disease suppression or increased plant biomass (Shen et al, 2019). The involvement of mediating rhizosphere microbiome in disease suppression was also demonstrated after inoculating endophytic Bacillus strains (Cheng et al, 2020;Uwaremwe et al, 2022).…”
Section: Reshaping Of Plant Microbiomementioning
confidence: 98%
“…The reactions were done in a total volume of 50µl with 0.4µM for the forward primer, 200 μM dNTPs (Fermentas) and 0.5 U Dream Taq DNA polymerase (Fermentas) and 1 × Taq DNA polymerase reaction buffer (Fermentas). The PCR reaction was performed following the thermal profile; initial denaturation at 94ºC for 2 minutes, 35 amplification cycles at 94ºC for 45 ºC, 55 ºC for 1 minute, 72 ºC for 1 minute, and the final extension at 72 ºC for 10 minutes.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%